2018
DOI: 10.12890/2018_000870
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Arthritis of the Ankle

Abstract: Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis complex (MTBC). Pulmonary TB is the most common form of presentation, but extrapulmonary tuberculosis (EPTB) contributes significantly to morbidity and mortality. Rarely, patients with EPTB develop a form of ankle or foot arthritis. The diagnosis of TB arthritis is often overlooked because of the insidious onset and the non-specific clinical symptoms. Prognosis is generally poor; early diagnosis and delivery of the most appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The literature revealed that hematological findings for musculoskeletal TB usually show decreased hemoglobin, mild lymphocytosis, and high ESR (erythrocyte sedimentation rate) [ 18 , 19 ]. The first detected change in plain radiography is peripheral marginal erosion of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The literature revealed that hematological findings for musculoskeletal TB usually show decreased hemoglobin, mild lymphocytosis, and high ESR (erythrocyte sedimentation rate) [ 18 , 19 ]. The first detected change in plain radiography is peripheral marginal erosion of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, TB is still a serious threat to human health. Pulmonary TB is the most common pattern of manifestaion, but Extrapulmonary TB (EPTB) contributes significantly to disability and mortality [3]. Timely diagnosis and correct treatment are critical to avoid functional disability.…”
Section: Case Reportmentioning
confidence: 99%
“…Extremely rare, patients with osteoarticular TB develop a form of bilateral ankles and feet arthritis. Additionally, because of its insidious onset and the atypical clinical symptoms that can mimic other diseases like subacute or chronic pyogenic arthritis, traumatic arthritis, rheumatoid arthritis, tuberculous rheumatism, osteochondrosis and benign bone tumors, the misdiagnosis rate is high [2][3][4]. Here we present a case of a 52-year-old man with bilateral feet and ankles tuberculous arthritis, misdiagnosed successively Rheumatoid Arthritis (RA) and Poncet's diease.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) is a chronic, granulomatous, and necrotizing disease caused by infection with Mycobacterium tuberculosis (MTB) [1]. Tuberculosis has always been one of the world's public health problems.…”
Section: Introductionmentioning
confidence: 99%